Humanizing Methodologies in Educational Research: Centering Non-Dominant Communities - Zuo, Xinyue (Journal of International Students, 2022)
XINYUE ZUO is a doctoral candidate in Teacher Education and Curriculum Studies at the University of Massachusetts Amherst. Her research focuses on language and literacy development of English language learners, second language acquisition, and educational bilingual interpreting. Email: xzuo@umass.edu.